APPLICATION OF UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) MODEL TO THE INTENTION TO USING MOBILE BANKING SERVICE - Bambang Sugiharto; Indah Umiyati; Noni Nissa Sholihah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
The aim of this research was to analyze the influence of performance expectations, effort expectations, and social influence on the intention to use mobile banking on mobile banking users. The study used three independent variables that are the performance expectations, effort expectations, and social influence, while intention to use mobile banking as a dependent variable. The sample of this research were society users of mobile banking in Subang Regency, West Java Province. Sampling incidental of Non-probability sampling was used as a sampling method with a total sample of 154 people. Validity, reliability, descriptive analysis, classical assumption test, and multiple regression analysis are used for this study. Statistical method for data testing using SPSS program 22. The result of this research indicates that performance expectations, effort expectations, and social influence have a positive effect on the intention in using either mobile banking, the result of tests on partial or simultaneously.